Iterative data detection and channel estimation for single-parity check-product coded MIMO wireless communications system - Muladi, Muladi; Fisal, N.; Yusof, S. K. (2005)
In iterative data-detection and channel-estimation algorithms, the channel estimator and the data detector recursively exchange the information order to improve the system performance. In this paper, maximum a posteriori based iterative data detection and pilot symbol assisted channel estimation of the single parity check product code for multiple antenna wireless communication is studied. Results show the algorithm can converge at a few iteration numbers and improve error probability performance of the system.